ATTITUDES AND PRACTICES ON CONTEXTUALIZATION AND LOCALIZATION OF ELEMENTARY TEACHERS IN EASTERN SAMAR DIVISION - Picardal,Benchel M; Lorna D. Capito, Ed. D., (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
With the full swing implementation of the K to 12 curriculum, contextualization and localization has become integral in support of the principle that learners learn best when lessons are presented with meaning and are relevant to their lives. Using the correlation research method and an adapted data gathering instrument, this study tried to examine the relationship between the attitudes and practices of 289 elementary school teachers in Oras Districts, Oras, Eastern Samar towards the implementation of contextualization and localization. It also examined set of profile characteristics which may have relationship with attitudes and practices. From the findings it was found that respondents are less anxious towards the implementation of contextualization and localization, making them receptive to change, and with high sense of community. Implementation practices have manifested a dissonance among the teachers in the districts indicating a need to create a synergy among schools. Further, it was revealed that age and length of service have positive weak relationship with respondents’ anxiety. Work position on the other hand indicated a negative weak relationship with sense of community and networking and linkages. Meanwhile, educational attainment and work position have shown negative correlation with practices while only anxiety among four attitudes evaluated was not significantly related with practices. It is recommended that implementation practices be improved by strengthening networks and linkages, formulating policies responsive to local situations, and providing relevant trainings to teachers.